(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of the current research is to know the attitudes of graduate students towards the quality of e-learning from the point of view of the students of the College of Imam Al-Adham (may Allah bless him) University. For the purpose of achieving the research goal, the researchers chose graduate students at the College of Imam Al-Adham (may Allah bless him) University, for the departments (Quranic readings, Islamic studies in English, Arabic language, advocacy and public speaking, Fiqh and its Foundations, Religion basics), which numbered (145) male and female students, as the researchers adopted the descriptive approach and considered the questionnaire a measuring tool consisting of two parts. The first part includes the general information of the study members represented in their personal and occupational variables such as (gender, academic qualification, and academicspecialty). As for the second part of the questionnaire, it included fifteen questions about e-learning and about the nature of students’ interaction with it in light of the nature of the research and the goals it seeks to achieve.Each paragraph was met with an answer that follows a five-point scale (R language scale): Strongly agree - Agree - Undecided - Disagree - Strongly disagree. Each response was given certain degrees to be processed statistically and distributed to a group of experts and judges specialized in educational and psychological studies and teaching methods to ensure the apparent honesty. The researchers also adopted the (R language) program to process the data statistically to extract the arithmetic mean, standard deviation and variance for all paragraphs.